Regulatory of Nuclear Power Plant: Environmental Safety Aspects on Nuclear Power Plant Operation - Beta, Werdi Putra Daeng (Proceeding International Conference on Global Resource Conservation, 2013)
Nuclear Energy Regulatory Agency also called BAPETEN is a national regulatory authority for nuclear energy uses in Indonesia. Regulatory of Nuclear Power Plants (NPPs) is one of BAPETEN authorities for nuclear energy uses, including NPP operation. Regulatory of NPP consists of 5 (five) steps, there are siting, construction, commissioning, operation, and decommissioning. In This paper, it would be discussed about regulatory of NPP, especially on environmental safety aspects in NPP operation. Operation of NPP is operating a nuclear reactor securely and safely in accordance with the design and purpose of its utilization for power generation. Operating NPP is essential to be observed considering the impact on the natural environment, urban and human population. Environmental safety aspects of nuclear power plant operations must meet the criteria and tight requirements in accordance with the legislations, international standards, assessments, in-depth and reliable studies, including environmental modeling and monitoring of the effluent for all pathways, also evaluation of radiation dose for members of public and emergency-response planning.Â Keywords: BAPETEN, NPP operation, environmental safety.